ADAM12-L is a direct target of the miR-29 and miR-200 families in breast cancer - Duhachek-Muggy, S.; Zolkiewska, Anna (My University, 2015)
ADAM12-L and ADAM12-S represent two major splice variants of human metalloproteinase-disintegrin 12 mRNA, which differ in their 3'-untranslated regions (3' UTRs). ADAM12-L, but not ADAM12-S, has prognostic and chemopredictive values in breast cancer. Expression levels of the two ADAM12 splice variants in clinical samples are highly discordant, suggesting post-transcriptional regulation of the ADAM12 gene. The miR-29, miR-30, and miR-200 families have potential target sites in the ADAM12-L 3' UTR and they may negatively regulate ADAM12-L expression. Methods: miR-29b/c, miR-30b/d, miR-200b/c, or control miRNA mimics were transfected into SUM159PT, BT549, SUM1315MO2, or Hs578T breast cancer cells. ADAM12-L and ADAM12-S mRNA levels were measured by qRT-PCR, and ADAM12-L protein was detected by Western blotting. Direct targeting of the ADAM12-L 3' UTR by miRNAs was tested using an ADAM12-L 3' UTR luciferase reporter. The rate of ADAM12-L translation was evaluated by metabolic labeling of cells with S-35 cysteine/methionine. The roles of endogenous miR-29b and miR-200c were tested by transfecting cells with miRNA hairpin inhibitors. Results: Transfection of miR-29b/c mimics strongly decreased ADAM12-L mRNA levels in SUM159PT and BT549 cells, whereas ADAM12-S levels were not changed. ADAM12-L, but not ADAM12-S, levels were also significantly diminished by miR-200b/c in SUM1315MO2 cells. In Hs578T cells, miR-200b/c mimics impeded translation of ADAM12-L mRNA. Importantly, both miR-29b/c and miR-200b/c strongly decreased steady state levels of ADAM12-L protein in all breast cancer cell lines tested. miR-29b/c and miR-200b/c also significantly decreased the activity of an ADAM12-L 3' UTR reporter, and this effect was abolished when miR-29b/c and miR-200b/c target sequences were mutated. In contrast, miR-30b/d did not elicit consistent and significant effects on ADAM12-L expression. Analysis of a publicly available gene expression dataset for 100 breast tumors revealed a statistically significant negative correlation between ADAM12-L and both miR-29b and miR-200c. Inhibition of endogenous miR-29b and miR-200c in SUM149PT and SUM102PT cells led to increased ADAM12-L expression. Conclusions: The ADAM12-L 3' UTR is a direct target of miR-29 and miR-200 family members. Since the miR-29 and miR-200 families play important roles in breast cancer progression, these results may help explain the different prognostic and chemopredictive values of ADAM12-L and ADAM12-S in breast cancer.
Citation: Duhachek-Muggy, S., & Zolkiewska, A. (2015). ADAM12-L is a direct target of the miR-29 and miR-200 families in breast cancer. Bmc Cancer, 15, 13. doi:10.1186/s12885-015-1108-1
Keywords: Metalloproteinase; Disintegrin; Alternative Splicing; Microrna; Post-Transcriptional Gene Regulation; Breast Cancer